Dynamics of Super Quantum Correlations and Quantum Correlations for a System of Three Qubits. (1st April 2016) - Siyouri, F.; Baz, M. El; Rfifi, S.; Hassouni, Y.
Abstract: The dynamics of quantum discord for two qubits independently interacting with dephasing reservoirs have been studied recently. The authors [Phys. Rev. A 88 (2013) 034304] found that for some Bell-diagonal states (BDS) which interact with their environments the calculation of quantum discord could experience a sudden transition in its dynamics, this phenomenon is known as the sudden change. Here in the present paper, we analyze the dynamics of normal quantum discord and super quantum discord for tripartite Bell-diagonal states independently interacting with dephasing reservoirs. Then, we find that basis change does not necessary mean sudden change of quantum correlations.